LabVIEWを用いたオーロラと大気光の光学観測制御システムの設計 - 青木, 猛; アオキ, タケシ; Aoki, Takeshi; 田口, 聡; タグチ, サトシ; Taguchi, Satoshi; 細川, 敬祐; ホソカワ, ケイスケ; Hosokawa, Keisuke (電気通信大学, 2013)
Computer-based control systems play an important role in instruments for the optical observations of the aurora and airglow. We developed the control system based on LabVIEW for our new optical instrument. The LabVIEW-based system controls the Electron Multiplier CCD camera and filter turret containing passband filters. Through the robust and flexible control of these equipments the instrument can adapt to a wide range of conditions, and obtain all-sky images over a long period of time. This article focuses on the important points of the control system. The instrument was set up at Longyearbyen, Svalbard in October 2011, and obtained valuable data during the first season as was expected. departmental bulletin paper